Raman-DIP (Deuterium Isotope Probing) reveals microbial metabolism at the single-cell level - Xu, J; Zhu, D; Ibrahim, A; Allen, C; Gibson, C; Fowler, P; Song, Y; Huang, W (American Chemical Society, 2017)
We illustrate that single-cell Raman microspectroscopy, coupled with deuterium isotope probing (Raman-DIP), provides a culture-independent and non-destructive approach to probe metabolic pathways of carbon substrates at the single-cell level. We find a distinguishable CD vibration band at 2070 - 2300 cm-1 in single-cell Raman spectra (SCRS) when Escherichia coli used deuterated glucose and Pseudomonas sp. used deuterated naphthalene as sole carbon sources. The intensity of the C-D band is proportional to the extent of deuteration in carbon source, and as low as 5% deuteration can be distinguished by analysis of SCRS. It suggests that Raman-DIP could be used to semi-quantitatively and sensitively indicate metabolisms of deuterated carbon source in microbes. A lower lipid conversion rate of deuterated naphthalene compared to that of deuterated glucose was observed, presumably owing to different anabolic pathways and membrane alteration. Apart from C-D band shift from C-H, SCRS also reveal several isotopic shifts of phenylalanine band of which the positions correlate well with a computational model. A reduction in phenylalanine deuteration in Pseudomonas sp. compared to that in E. coli is due to dilution effect of deuterated carbon source via different phenylalanine pathways in Pseudomonas sp.. Collectively, we demonstrate that Raman-DIP can not only indicate metabolic activity using deuterated carbon sources, but also reveal different metabolic pathways by analysing SCRS. Harnessing such low-cost and versatile deuterated substrates, Raman-DIP has the potential to probe a wide range of metabolic pathways and functions at the single cell level.